A dinâmica política, econômica e social do rio São Francisco e do seu vale - Camelo Filho, José Vieira (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2011)
The São Francisco River was always an important linking channel among Brazil Northeast, Southeast and Centro-Oeste regions, through fluvial navigation. Strategically, this river and its branches have contributed to the control and settlement in the interior of Brazil, where, along history, the large and the small properties were constituted. Both are responsible for the economic and social underdevelopment of the São Francisco Valley. Its economy, till the first half of the twentieth century, was supported by the extensive cattle growing and by the subsistence agriculture. The possession or the access to the land, for most part of the population, has been a big challlenge to the Government. Along the last 50 years, the water of the Old Chico has become one of the biggest richness of the São Francisco Valley and the main raw material to its development that has effectively begun with the generation of electric energy in Paulo Afonso. From the beginning of the eighty and ninety decades, the irrigation process has been intensified, aiming, in especial, the production of fruits in the irrigation perimeter of Petrolina and Juazeiro, west of Bahia State, in the Jaíba Project and Pirapora, in Minas Gerais State. However, during the last years, the Project of Transposition of Water from the São Francisco River to other hydrographic basins of the semi arid region has got prominence.